2021
DOI: 10.1017/s0025315421000242
|View full text |Cite
|
Sign up to set email alerts
|

Trophic niches and diet shifts of juvenile mullet species coexisting in marine and estuarine habitats

Abstract: Food partitioning among coexisting species is often considered advantageous to minimize niche overlap and avoid inter-specific competition. Congeneric fish species such as the mullets Mugil curema and Mugil liza, which co-occur across marine and estuarine habitats, are good models to evaluate resource use and niche overlap or partitioning. We used stomach contents (SCA) and stable isotope analysis (SIA) to assess potential trophic shifts and changes in niche overlap associated with the mullets transitioning fr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 11 publications
(3 citation statements)
references
References 81 publications
0
2
0
Order By: Relevance
“…In addition to morphological characteristics, difference in prey availability (e.g. seasonal difference: Heng et al., 2019; Waraniak et al., 2019, spatial difference: Garcia et al., 2018; Vollrath et al., 2021) has previously been shown to affect the degree of dietary overlap between fish species. Spatial differences in biotic factors may explain why the same species pair did not show a consistent relationship across sampling sites (e.g.…”
Section: Discussionmentioning
confidence: 99%
“…In addition to morphological characteristics, difference in prey availability (e.g. seasonal difference: Heng et al., 2019; Waraniak et al., 2019, spatial difference: Garcia et al., 2018; Vollrath et al., 2021) has previously been shown to affect the degree of dietary overlap between fish species. Spatial differences in biotic factors may explain why the same species pair did not show a consistent relationship across sampling sites (e.g.…”
Section: Discussionmentioning
confidence: 99%
“…Direct observations revealed that the contribution rates of Diptera, Orthoptera, and Lepidoptera were highest, while stable isotope analysis showed that the contribution rates of Orthoptera, Hemiptera, and Hymenoptera were highest. This difference can be explained by methodological differences; stable isotope analyses reflect the food resources assimilated by animals rather than the food consumed by animals [42,43], while the direct observation method records food resources that are consumed. Lepidoptera had the lowest contribution rate in the stable isotope analysis (2.29% for S. yunnanensis and 4.12% for S. nagaensis).…”
Section: Discussionmentioning
confidence: 99%
“…In order to obtain an SOM sample, about 2 cm of surface sediment was removed using a 10 cm diameter plastic pipe. These organic sources were collected to serve as proxies of the isotopic variability of microalgae and debris (Fry, 2006;Vollrath et al, 2021), which constitutes the main sources of primary organic matter sustaining consumers in sandy beaches along the studied coastal plain (Pinotti et al, 2014;Garcia et al, 2019aGarcia et al, , 2019b. Other primary producers, such as floating aquatic macrophytes, seagrasses and macroalgae beds, are usually absent in the sandy beaches of this coastline (Odebrecht et al, 2010).…”
Section: Field Collections and Sample Processingmentioning
confidence: 99%